1992
DOI: 10.1520/jfs13298j
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine Analysis in Single Collection Urine Specimens

Abstract: Controlled and uncontrolled fluid intake studies were conducted on series of volunteers over the 6 or 12 h of the study periods. Urine specimens were obtained from each subject randomly or at specified times relative to fluid ingestion. Creatinine analysis performed by a modification of the Abbott TDx procedure demonstrates that the values obtained from single collection specimens fall almost in the same range as the values from 24 h pooled collection specimens. The creatinine concentration can be used to indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 2 publications
2
18
0
2
Order By: Relevance
“…However, the 2.5% percentile of the urine-creatinine concentration for women (189 mg/L) was clearly below suggested cut-off levels of <300 mg/L [2], of <250 mg/L [3] and of <200 mg/L [4,5] and the same is true for men (256 mg/L 2.5% percentile) when using cutoffs of >250 mg/L. This situation is not acceptable since it bears the risk of a high rate of false classifications between physiological and adulterated urine samples.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, the 2.5% percentile of the urine-creatinine concentration for women (189 mg/L) was clearly below suggested cut-off levels of <300 mg/L [2], of <250 mg/L [3] and of <200 mg/L [4,5] and the same is true for men (256 mg/L 2.5% percentile) when using cutoffs of >250 mg/L. This situation is not acceptable since it bears the risk of a high rate of false classifications between physiological and adulterated urine samples.…”
Section: Discussionmentioning
confidence: 75%
“…The latter could clearly be attributed to a very slender habitus of the women tested. The consequences would have been: 18 false-positives (26% out of 70 measurements) when applying a cut-off of <300 mg/L according to [2], 13 false-positives (19%) when using a cut-off of <200 mg/L like given in [4,5] and still 2 false-positives (3%) with a cut-off of <100 mg/L. The latter (3%) are still a relatively high rate of false-positives from the forensic point of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Most of these applications, however, have been designed with the specific aim of avoiding false negative results in drug screening programs due to very dilute urine specimens. 22,29,30 Few, however, have attempted to employ creatinine adjustments in the clinical setting. Manno et al 23 reported that the Syva EMIT-d.a.u.…”
Section: Discussionmentioning
confidence: 99%
“…Dilution of urine either by drinking excessive amounts of water ("internal dilution") or by adding water to a urine sample ("external dilution") or by taking diuretics or other special teas is a serious problem in drugs of abuse (DOA) testing [1][2][3][4][5]. Many subjects use this tampering method in order to dilute drugs in urine to levels that are below cutoff values in order to obtain false negative results [6].…”
Section: Introductionmentioning
confidence: 99%